A questão dos resíduos sólidos urbanos em Curitiba: bases para a discussão e técnica de cenários - Melo, Lucas Araújo de (2008)
The matter about Municipal Solid Waste has been one of the main worries of mankind, regarding the environment and human development. The problems caused by solid waste have environmental, social and economics dimensions, and those are specially evident when studying poor countries. At the city of Curitiba, the level of discussions regarding solid waste problems have increased among the academic and political community. The Caximba Sanitary Landfill, the only form of destination of the city solid waste, is about to completely fulfill its capacity, and the difficulty on finding viable areas for building a new sanitary landfill enhances the problem. One way of dealing with waste disposal problem is to develop programs and management strategies such as programs enhancing recycling and composting and environmental educational programs, what contributes to reduce the amount of waste to be disposed. In order to lessen the negative impacts generated by the growing waste production, it is important that proper management be done. According to Sokka et al., proper management depends on efficient planning, based on the understanding of the historical evolution process of solid waste generation. So it is important that solid historical database to be maintained, regarding waste production. The scenario technique has been used by governments and enterprises as a tool for strategical planning in many domains. In this study, the historical production of municipal solid waste in Curitiba was presented and discussed, and the scenario technique was presented as an approach to waste management planning process. An example of the technique was done for the case study of Curitiba. To build the scenarios, municipal solid waste production in Curitiba was projected to 2020, by correlating socioeconomic factors to solid waste generation. Similar approaches were used in other studies. Six scenarios were built from different strategies that could be applied to solid waste management (minimization, recycling and composting), and the effects in the future of each scenario were analyzed and compared to other scenarios, in terms of environmental impacts, management costs, volume and weight of waste produced. The information generated with this study may contribute to solid waste management in Curitiba, for defining management objectives and the best way to reach them, and for developing strategies and policies.